A technoeconomic analysis of centralised and distributed processes of ammonia dissociation to hydrogen for fuel cell vehicle applications. (31st May 2019) - Nasharuddin, Razyq; Zhu, Mingming; Zhang, Zhezi; Zhang, Dongke
Abstract: Ammonia (NH3 ) has been proposed as a hydrogen (H2 ) carrier for energy services in the carbon-constrained future. This paper presents a technoeconomic feasibility study of using NH3 as H2 carrier for fuel cell vehicles (FCVs) applications. Two cases with different scales of anticipated operations: (1) centralised installation (1000 tonnes day −1 ) and (2) distributed refuelling station (500 kg day −1 ), were considered. Aspen HYSYS v8.6 was utilised to simulate the processes. The H2 production cost, internal rate of return, payback period and net present value were examined and compared. The results indicate the centralised H2 production is both technically and economically feasible while distributed H2 production, falling foul of economy of scale, is not economically viable. The overall H2 production cost of the centralised H2 production can reach as low as USD 5.50 kg −1 H2 accounting for capital expenditure, operating expenses, and decommissioning costs. The sensitivity analysis shown that the overall H2 production cost is highly sensitive to NH3 price and moderately affected by utility price and various corporate tax rates considered. Highlights: Technoeconomic feasibility of NH3 to H2 conversion for FCVs is systematically studied. At USD 5.50 kg −1 H2, centralised H2 production from NH3 is economically viable. Distributed H2 production by NH3 dissociation at refuelling station is not feasible. The cost of H2 production is most sensitive to NH3 price, followed by utility cost.